Consumers' perception of reduced calorie meals: How low is "Low-Calorie"?. Issue 6 (1st November 2020) - Sun, Xiaodi; Behnke, Carl; Almanza, Barbara; Ghiselli, Richard; Byrd, Karen
ABSTRACT: With consumers becoming increasingly health conscious, the demand for reduced calorie food has significantly increased over the years. However, the definition of low-calorie food remains unclear. Therefore, the purpose of this study was to investigate consumers' perception of reduced calorie meals, from the perspective of the maximum calorie level that consumers would consider as "low-calorie." Survey data were collected using MTurk. In addition to respondents' perception of the calorie count of low-calorie food when eating out and eating at home, respondents' attitude toward low-calorie food, behaviors about consuming low-calorie food and exercise frequency, and demographic information were also assessed in the survey. The results demonstrate that consumers' calorie perception of low-calorie food served in restaurants is consistent among different types of restaurants. Moreover, consumers believe that a low-calorie meal served in restaurants should be under 367 calories for breakfast, 500 calories for lunch, and 677 calories for dinner. Lastly, consumers perceive home-cooked meals to be lower in calories than restaurant food. This study is the first attempt to explore consumers' definition of a low-calorie meal served in restaurants. The findings will provide guidance to restaurant operators in designing menus, and help policymakers better understand the ongoing need to develop a sound and comprehensive definition for the term "low-calorie."